2011
DOI: 10.1021/jp2065826
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Capillary-Driven Flow in Open Microchannels

Abstract: The dynamics of capillary-driven flow was studied for water and water–glycerol mixtures in open hydrophilic microchannels (embedded in a hydrophobic matrix). The position of the advancing meniscus was recorded as a function of time using high speed microscopy and compared with the Washburn equation. The square of the position of the liquid front increased linearly with time, as predicted by Washburn. For a channel of the same depth, irrespective of the shape of the channel cross-section (rectangular or curved)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
143
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(167 citation statements)
references
References 52 publications
19
143
1
4
Order By: Relevance
“…We find that fits to the numerical solution of the exact differential equation describing capillary rise, neglecting the fingers, up to the point where the fingers reach the ends of the channels can describe the rise of the central meniscus of the liquid in both of these cases. We also find that the friction in the openchannel case is consistent with a non-rigidified liquid-air interface rather than for a rigidified boundary as recently reported for imbibition into horizontally mounted open microchannels (Yang et al, 2011).…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…We find that fits to the numerical solution of the exact differential equation describing capillary rise, neglecting the fingers, up to the point where the fingers reach the ends of the channels can describe the rise of the central meniscus of the liquid in both of these cases. We also find that the friction in the openchannel case is consistent with a non-rigidified liquid-air interface rather than for a rigidified boundary as recently reported for imbibition into horizontally mounted open microchannels (Yang et al, 2011).…”
Section: Introductionsupporting
confidence: 89%
“…However, Girardo et al (2012) found that fingers do not seem to induce appreciable extra dissipation in the early stage of microcapillary imbibitions in horizontally mounted smooth microchannels. It is also of note that the fitted values of the viscous coefficient a for the open channels are a factor 2 and 3 lower (for the 400 µm and 600 µm wide open channels) than would be expected for a rigidified liquid-air boundary, as required by Yang et al (2011) to explain the dynamics of capillary flow in their horizontally mounted open narrow microchannels. This indicates that a non-rigidified liquid-air interface best represents the flow in our lower aspect ratio channels.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Particularly, for channel width below the water capillary length (i.e., 2.7 mm), the interfacial shear stress increases as the channel size decreases. Investigating the speed of the advancing meniscus flooding an open hydrophilic channel, Yang et al 30 found a good agreement between experimental data and theoretical predictions when a no-slip boundary condition was assumed at the liquid-air interface.…”
Section: Introductionmentioning
confidence: 89%